2018
DOI: 10.18632/oncotarget.26179
|View full text |Cite
|
Sign up to set email alerts
|

XPO1 inhibition by selinexor induces potent cytotoxicity against high grade bladder malignancies

Abstract: Treatment options for high grade urothelial cancers are limited and have remained largely unchanged for several decades. Selinexor (KPT-330), a first in class small molecule that inhibits the nuclear export protein XPO1, has shown efficacy as a single agent treatment for numerous different malignancies, but its efficacy in limiting bladder malignancies has not been tested. In this study we assessed selinexor-dependent cytotoxicity in several bladder tumor cells and report that selinexor effectively reduced XPO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 51 publications
(52 reference statements)
4
14
0
Order By: Relevance
“…S15). Decreases in the expression levels of XPO1 protein by Selinexor are reported in other studies 24 and are associated with decreased cell proliferation and apoptosis, mediated by survivin. Immunofluorescence staining confirmed that p27 was localized predominantly in the nucleus in cells that were exposed to Selinexor, Fig.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…S15). Decreases in the expression levels of XPO1 protein by Selinexor are reported in other studies 24 and are associated with decreased cell proliferation and apoptosis, mediated by survivin. Immunofluorescence staining confirmed that p27 was localized predominantly in the nucleus in cells that were exposed to Selinexor, Fig.…”
Section: Resultssupporting
confidence: 69%
“…Using the approach of selective inhibition of nuclear export (SINE) with siRNA mediated knockdown of XPO1, our results show that in order to execute its anti-apoptotic function, p27 protein must be stabilized in the nucleus and the combined inhibition of cell cycle progression and XPO1 activity, maintains p27 nuclear localization and promotes tumor suppressor function. These findings are of interest as SINE agents such as Selinexor show promising clinical activity against multiple myeloma growth 32 , bladder cancer 24 as well as other types of cancer that is mediated through the survivin pathway. Of note, Selinexor did not achieve single agent activity against the Pediatric Preclinical Testing Consortium osteosarcoma xenograft tumor panel 33 .…”
Section: Discussionmentioning
confidence: 96%
“…To assess if canine OS cells responded similarly, we treated four cell lines with 0.1% DMSO, 0.1 μM verdinexor, or 1 μM verdinexor for 24 hours and evaluated XPO1 expression via quantitative real‐time PCR and Western blotting (Figure 4). Similar to previously published results, we found that treatment with verdinexor caused a reduction in XPO1 protein expression 35,36 . Additionally, XPO1 mRNA was significantly increased in all cell lines tested.…”
Section: Resultssupporting
confidence: 91%
“…Concordant with our data, XPO1 is overexpressed in human OS compared with normal tissues 19 . Similarly, XPO1 is overexpressed in a number of human cancers such as gastric, oesophageal, bladder, and multiple myeloma and increased XPO1 expression has been associated with poor survival outcome 22,34‐36 . Although the prognostic impact of XPO1 expression in canine OS was not evaluated in this study, we demonstrated that XPO1 overexpression is common event in canine OS cells and as such, XPO1 may represent a relevant target for therapeutic intervention.…”
Section: Discussionmentioning
confidence: 65%
“…Molecular and genetic alterations in bladder cancer have been extensively studied in the past decades. Clinicopathological features, including tumor grade and stage have been shown to be linked to biological and genetic mechanisms [2224]. However, clinical challenges still exist for bladder cancer making it crucial to focus on new prediction methods based on the molecular targets.…”
Section: Discussionmentioning
confidence: 99%